2020
DOI: 10.1080/09544828.2020.1743244
|View full text |Cite
|
Sign up to set email alerts
|

Designers’ professional identity: personal attributes and design skills

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights. Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 183 publications
0
21
0
2
Order By: Relevance
“…To evaluate these differences we adopt a detailed DPI framework, which consists of Personal Attributes (PA) and Design Skills (DS) (Kunrath, Cash, andLi-Ying 2017, 2016). Semi-structured interviews were held with designers and design engineers to evaluate self-perception, and design professors and design managers to evaluate socialperception 1 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To evaluate these differences we adopt a detailed DPI framework, which consists of Personal Attributes (PA) and Design Skills (DS) (Kunrath, Cash, andLi-Ying 2017, 2016). Semi-structured interviews were held with designers and design engineers to evaluate self-perception, and design professors and design managers to evaluate socialperception 1 .…”
Section: Methodsmentioning
confidence: 99%
“…We synthesise insights from the extensive literature review reported by Kunrath et al (2016; in order to operationalise a list of elements capturing the widest range of relevant DPI constructs described in the design literature. Specifically, we separate confidence into self-and professional-aspects, as well as highlighting Motivation and Creativity as critical aspects of design work .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…La motivación se muestra en la literatura como una competencia crítica en el desempeño de los diseñadores (Robinson, Sparrow, Clegg, & Birdi, 2005). Se define como la participación en una actividad con un interés y percepción de disfrute inherentes y con una asociación a un resultado de valor (Kunrath, Cash, & Kleinsmann, 2020). La motivación se entiende también como una fuerza que mueve la interacción y pertenece a la persona, pero que también puede estar causada por el sistema (Schibelsky, Piccolo, Cecília, & Baranauskas, 2012).…”
Section: El Diseñador Frente a La Creatividad Y Circularidadunclassified
“…Después de terminar el trabajo con los dos problemas, los participantes tuvieron que responder un cuestionario con preguntas de tipo escala Likert para indicar su nivel de motivación para cada uno de los productos a diseñar, cómo de relevantes eran para ellos, su afinidad hacia el producto y el nivel de conocimiento que consideraban que tenían sobre ellos (Figura 43). La autoevaluación ha sido utilizada comúnmente en numerosos estudios como, por ejemplo, en Grewal, Hmurovic, Lamberton, & Reczek ( 2019) o Kunrath et al (2020). Tracey & Hutchinson (2016) subrayan la importancia de la conciencia de uno mismo como diseñador.…”
Section: Figura 41 Enunciado Proporcionado a Los Participantes En Elunclassified